ANALISIS PENYEBAB KERETAKAN WINDSHIELD TERHADAP KERUSAKAN HEATING ELEMENT DI PESAWAT AIRBUS 330 - Candra, Riki (Motor Bakar : Jurnal Teknik Mesin, 2025)
Flight safety is important to ensure passengers safely reach their destination. Aircraft have several parts in its maintenance, one of which is the windshield. Cracks in the windshield are often found due to damage to the heating element system. The rate of addition of heating element resistance is 0.133 /h and the rate of addition of windshield cracks to the number of flying hours is 0.02 mm/h. The measurement results show that the left and right windshield 9N-ALY registration aircraft with heating elements function properly. The left windshield of PK-GPV registration is in zone B with a dielectric yield of 0.8 mA (close to the limit of 1 mA). The measurement results for the PK-GPX registration aircraft stated that the left windshield had to be replaced. These results were obtained because the insulation test on the heating element was 78.8 Mohms (below the minimum limit of 100 Mohms). A low insulation test will cause the heating element system to have low insulation quality and leakage between the interconnections. If the windshield is not replaced, there will be a risk of failure of the heating element system and cracks on the windshield will occur.